Human response patterns: a comprehensive translation to Portuguese of the taxonomy I - Cruz, Isabel Cristina Fonseca da; Cruz, Diná de A.L.M. da (Revista da Escola de Enfermagem da USP, 1991)
This study presents a translation to Portuguese of the Human Response Patterns which are conceptual framework of Taxonomy I proposed by North American Nursing Diagnosis Association.